Teachers’ Challenges and Perspectives towards Online Applications for Online Learning - Koroh, Riyo Pasca Alexander; Yamin, Moh; Rosalina, Elsa (Universitas Pahlawan Tuanku Tambusai, 2024)
This research seeks to identify perspectives and challenges in using online learning applications. The sample for this research was 3 EFL teachers at SMP Santa Maria Banjarmasin. This research uses a qualitative approach to obtain data. The instrument used in this research consisted of 8 open-ended questionnaires created online using Google Forms. The data is then collected, analyzed, and described. This research found that, SMP Santa Maria Banjarmasin teachers used online learning applications such as Zoom, Google Classroom, WhatsApp, Google Meet, and Canva. The challenges come from a need for more skills in using Zoom's features, time constraints, and a need for features on the free account. Teachers believe that online learning can be implemented with thorough preparation because it is beneficial for education in the future. Therefore, the researcher suggests that further research use a more detailed methodology in collecting samples and analyzing data to further serve for in-depth findings about online learning applications.